Glass forming regions, structure and properties of lanthanum barium germanate and gallate glasses - Calzavara, Florian; Allix, Mathieu; Dussauze, Marc; Jubera, Véronique; Nalin, Marcelo [UNESP]; Cardinal, Thierry; Fargin, Evelyne (Elsevier, 2021)
Glass forming regions in the system GaO3/2 – GeO2 – LaO3/2 – BaO have been explored using aerodynamic levitation coupled to laser heating synthesis technique. Structure property relationships have been established between the thermal and optical properties of the resulting glass thanks to Raman and Infrared vibrational spectroscopies. The germano-gallate glass networks are mainly made of three-dimensional interconnected corner shared GeO4 and GaO4 tetrahedra forming Ge – O – Ge and Ga – O− – Ge bridges in which gallium tetrahedral GaO4 units are charged-compensated by barium and lanthanum cations. In GeO2-rich compositions, the excess of positive charges produces mainly non-bridging oxygens on germanate moieties, leading to a depolymerization of the glass network. In the case of gallium rich compositions, the infrared cut-off is red-shifted as compared to the germanate glasses, in accordance with the disappearance of germanium associated entities such as germanium and gallium bridges or germanium sites with non-bridging oxygen both vibrating at higher wavenumber.
Keywords: Aerodynamic levitation coupled to laser heating; Germano-gallate glasses; Glass structure; Heavy-metal oxide glasses; Vibrational Infrared and Raman spectroscopies